Використання маркетингових стратегій в ресторанному господарстві в умовах економічної кризи - Литвиненко, Тамара Євгенівна; Литвиненко, Ярослав Васильович (My University, 2013)
У статті розглядається проблема подальшого розвитку сфери ресторанного господарства в сучасних умовах економічної кризи в Україні. Подальший розвиток цієї сфери не можливий без маркетингових досліджень, розрахунку стратегії подальшого розвитку цих закладів. Визначаються основні напрямки проведення маркетингового дослідження. Особливе значення має проведення маркетингового дослідження для визначення ступені конкуренції на ринку та місця на ньому певного закладу ресторанного господарства. This article considers the problem of the further development of restaurant business in today's economic crisis in Ukraine. The gradual expansion of the network of restaurants has positive and negative features, especially the construction of new enterprises. Expansion of the network and the number and quality of services which are provided, can improve services, increase its spare time. Further development in this area is not possible without market research, calculation strategy for further development of these enterprises. The basic directions of the market research, which include analysis of the market for such services, requirements analysis and characteristics of clients, subject to change in demand, the analysis of changes in priorities, tastes, the influence of various factors in the process of changing customer service and more are determined. Special importance is the market research for determination of the degree of competition in the market and its place of the restaurant on it.
Keywords: ресторанне господарство; заклад ресторанного господарства; маркетингова стратегія; контингент споживачів; політика обслуговування споживачів; restaurant management; restaurant management institution; marketing strategy; contingent of consumers; customer service policy